ENGINEERING-GEOLOGICAL CONDITIONS OF DNIEPER VALLEY ON AREA OF DNIEPER WATER-STORAGE BASIN - Demchyshyn, M.G.; Kril, T.V. (Institute of Geological Sciences, NAS of Ukraine, 2015)
The features of engineer-geological conditions on a site of break of Dnieper through the Ukrainian shield are considered. This territory tested anthropogenic influence since olden times. Most changes happened after building of a dam of multifunction Dnieper water-storage basin. The problem of navigation was decided at flooding of the Dnieper rapids. The engineer-geological problems of adjoining to this area of valley territory are also related to distribution of grounds of loess structure (periglyacial area of the Dnieper glacier).